Molecular and Silica‐Supported Mo and W d0 Imido‐Methoxybenzylidene Complexes: Structure and Metathesis Activity. Issue 10 (2nd October 2019) - Zhizhko, Pavel A.; Toth, Florian; Gordon, Christopher P.; Chan, Ka Wing; Liao, Wei‐Chih; Mougel, Victor; Copéret, Christophe
Abstract: 5‐Coordinated methoxybenzylidene complexes M(=NAr)(=CH−C6 H4 − o ‐OMe)(O t BuF3 )2 (Ar=2, 6‐ i Pr2 C6 H3 ; t BuF3 =CMe2 (CF3 )) of Mo (1mMo ) and W (1mW ) were synthesized by cross‐metathesis from the corresponding neophylidene/neopentylidene precursors and o ‐methoxystyrene.1mMo and1mW were grafted onto the surface of silica partially dehydroxylated at 700 °C to give well‐defined silica‐supported alkylidenes (≡SiO)M(=NAr)(=CH−C6 H4 − o ‐OMe)(O t BuF3 ) (M=Mo (1Mo ), W (1W )). Supported methoxybenzylidene complexes were tested in metathesis of cis ‐4‐nonene, 1‐nonene, and ethyl oleate, and compared to their molecular precursors and supported classical analogs (≡SiO)M(=NAr)(=CHCMe2 R)(O t BuF3 ) (M=Mo, R=Ph (2Mo ), M=W, R=Me (2W )). Both grafted complexes1Mo and1W show significantly better performance as compared to their molecular precursors1mMo and1mW but are less efficient than the classical 4‐coordinated alkylidenes2Mo and2W . Noteworthy, both1Mo and1W can reach equilibrium conversion in metathesis of cis‐ 4‐nonene at catalyst loadings as low as 50 ppm. Abstract :